Classroom Management: Learners’ Motivation and Organize The Learning Environment of PAI - Sulaiman Sulaiman (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2017)
Classroom management is the key to success and improves the quality of PAIlearning in the classroom. Learners are potential classes who can be utilized througheffective classroom management. Teachers are required to have classroommanagement skills to optimize the PAI learning process in the classroom effectively.Conducive, challenging and inspiring classroom situations can develop PAI learningmotivation. This is the positive implication of effective classroom management on PAIlearning